1972
DOI: 10.1104/pp.50.6.698
|View full text |Cite
|
Sign up to set email alerts
|

The Cupric Ion as an Inhibitor of Photosynthetic Electron Transport in Isolated Chloroplasts

Abstract: The role of copper in photosynthetic organisms depends greatly on its concentration. Copper, as cupric ion, in trace amounts is an essential micronutrient for algae and higher plants (17,20) and is an essential constituent of several enzymes such as polyphenol oxidase (3) and plastocyanin (8), a component of photosynthetic electron transport. Concentrations higher than 1 /tm are increasingly toxic to algal and higher plant tissues (4, 13). Cupric sulfate has been extensively used as an algaecide since the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 19 publications
(27 reference statements)
6
63
0
2
Order By: Relevance
“…The earliest report stated the proximity of a Cu binding site to the oxygen evolving complex (OEC) [6]. Further studies confirmed the existence of a highly sensitive site for Cu-inhibition on the oxidizing side of PSII [7][8][9]. Copper ions have been even suggested to substitute calcium and manganese ions in the OEC [10].…”
Section: Introductionmentioning
confidence: 98%
“…The earliest report stated the proximity of a Cu binding site to the oxygen evolving complex (OEC) [6]. Further studies confirmed the existence of a highly sensitive site for Cu-inhibition on the oxidizing side of PSII [7][8][9]. Copper ions have been even suggested to substitute calcium and manganese ions in the OEC [10].…”
Section: Introductionmentioning
confidence: 98%
“…Copper is an essential micronutrient for algae and higher plants and is an essential constituent of a number of plant enzymes (21). Copper at concentrations higher than I ,UM is increasingly toxic to algal and higher plant tissues (10,23 (10,19,26) and to inhibit photosynthetic electron transport in isolated chloroplasts (6,12). The basis for Cu toxicity in plants is largely unknown.…”
Section: Methodsmentioning
confidence: 99%
“…Cu2+ introduced as a trace contaminant from distilled or deionized H20 would also be highly effective. This effect and those described previously (5,22) mayr well be of significance in areas of high natural abundance of Cu + or in areas where it is present as a pollutant.…”
Section: Resultsmentioning
confidence: 77%
“…shown that it can inhibit election transport at the oxidizing side of PSII (5) and through a direct inactivation of ferredoxin (22). A preliminary report (25) has delineated the effect of Cu2+ on CF1-dependent reactions of spinach chloroplasts.…”
mentioning
confidence: 99%